Analisis Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan : Studi Pada Dinas Perdagangan Dan Perindustrian Kabupaten Flores Timur - Olivya Andreas; Prayekti ` Prayekti; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine work motivation, work environment, and work stress on employee job satisfaction. This research method uses a questionnaire. The population in this study were all employees working at the East Flores Regency Industry and Trade Office, totalling 50 employees. The sampling technique in this study is saturated sampling. The data source of this research is primary data. Test the quality of the data using validity test, reliability test. and Classical Assumption Test. The data analysis technique in this study used Multiple Linear Regression Analysis, Statistical Test T, Statistical Test F. The research finding are simultaneously the variables of work motivation, work environment, and work stress have a significant effect on employee job satisfaction.